Métricas e indicadores de sustentabilidade aplicados a processos e produtos baseados em microalgas - Deprá, Mariany Costa (2022)
Processes and products with a sustainable character are increasingly urgent to deal with the global questions of energy scarcity and environmental deterioration. Given this approach, substantial efforts have been made to investigate or expand the potential of processes and products based on microalgae with a sustainability aspect. However, while these microorganisms have been recognized for their capacity to bioconvert carbon dioxide (CO2) concomitant to biomass production with composts of high commercial interest, these processes still face complex challenges that be resolved. Technical barriers such as the microalgae performance in high concentrations of CO2, cultivation operational parameters, energy demand, beyond the difficulty of establishing cultivation on an industrial scale, can test the truthful environmental and economic processes. In view of this, the work aimed to: (1) understand the operational implications and technical details of photosynthetic culturing systems; (2) evaluate the microalgae under different CO2 concentrations; (3) evaluate the influence of CO2 loads on the carbon footprint in photobioreactors; (4) estimate potential carbon credits from microalgal processes; (5) determine the sustainability performance of microalgal-based processes and products, and (6) standardize methodologies for quantifying sustainability metrics and environmental impact indicators applied to industrial and agricultural systems. The kinetic performance of the microorganism was considered through free CO2 profiles in the liquid phase of the system, measurements of gas-phase concentrations, and stoichiometric conversion to biomass. In addition, the sustainable performance of microalgae-based processes and products were evaluated under the use of mathematical modelings such as life cycle assessment and carbon footprint. The results obtained demonstrated the importance of the cultivation operational parameters evaluated in the carbon fixation in biomass as well as in the overall carbon footprint of the system. The microalgae performed satisfactorily under stressful culture conditions (with injections higher than 15% CO2). On the other hand, the masses of captured carbon and carbon credits showed better performances for carbon injection conditions below 5% CO2. With the help of life cycle assessment and carbon footprint tools, microalgae-based processes and products did not prove to be environmentally sustainable, as they are excessive in terms of energy, water, and nutrients. In energy terms, the hotspots of the process were the cultivation, harvesting, and drying stages. However, it was identified that by using renewable energy, environmental impacts can be reduced by up to 95% for renewable energy matrices. Regarding the culture systems, the best environmental performance was attributed to the open ponds. However, in direct comparison to closed systems, fermenters and tubular photobioreactors presented the best environmental indicators. As for the products, the stages of extraction and yield of intracellular compounds negatively influence environmental performance. Finally, this work provides numbers quantitative and adequate methodology to determine sustainability metrics and indicators for microalgal projects considering the current stage of commercial technology.